169k views
3 votes
3(2x +5) = 3x+ 15 what is the answer plz help me ​

User Mwfire
by
5.0k points

2 Answers

0 votes

Answer:

x=0

Explanation:

3 (2 + 5) = 3 + 15

(3) (2) + (3) (5) = 3 + 15

6 + 15 = 3 + 15

6 + 15 − 3 = 3 + 15 − 3x

3 + 15 = 15

3 + 15 − 15 = 15 − 15

3x = 0

devide, and then you have x=0

User Metaforge
by
4.7k points
5 votes

Answer:


x = 0

1. 3 (2
x + 5) = 3
x + 15

(3) (2
x) + (3) (5) = 3
x + 15

6
x + 15 = 3
x + 15

2. 6
x + 15 − 3
x = 3
x + 15 − 3x

3
x + 15 = 15

3. 3
x + 15 − 15 = 15 − 15

3x = 0

4.
(3x)/(0) =
(0)/(3)

Answer = 0

User Edder
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.